Expression and Characterization of Trastuzumab in Baby Hamster Kidney Cell Line to Check its Anti-Cancer Activity in HCC 1954 - Muzammal Mateen Azhar; Tahir Maqbool; Awais Altaf; Afsheen Akbar; Imtiaz Mustafa; Zahid Habib Qureshi (Journal of Liaquat University of Medical & Health Sciences, 2025)
OBJECTIVE: To investigate Trastuzumab’s production and anti-cancer effects on hepatocellular carcinoma (HCC1954) cells. METHODOLOGY: This study was conducted in IMBB/CRiMM, The University of Lahore, Pakistan. A humanized IgG1 monoclonal antibody (Trastuzumab) with a high affinity for the extracellular domain of HER2 was produced. Antibody includes humanized sequences. Its antiproliferative effect was quantified using the MTT assay on the Hepatocellular carcinoma (HCC1954) and BHK cells. SDS-PAGE confirmed HER2 protein expression. Statistical Analysis was performed using the Social Package for the Statistical Sciences (SPSS) version 17.0 (SPSS, Chicago, IL, USA). RESULTS: The expressed monoclonal antibody (Trastuzumab) exhibited anti-cancer activity, specifically targeting and inhibiting cell proliferation in the HCC1954 breast cancer cell line. The MTT quantified the antibody’s antiproliferative effects, & SDS-PAGE confirmed HER2 protein expression. The quality & expression levels of Trastuzumab were optimized, paving the way for its local manufacturing and use as a therapeutic option in Pakistan. CONCLUSION: Trastuzumab effectively targets HER2, disrupting cancer-promoting pathways, which may provide therapeutic benefits. The study supports the feasibility of local production in Pakistan, which could improve treatment access and affordability for patients.